A blockchain- and IoT-based smart product-service system for the sustainability of prefabricated housing construction. (1st March 2021) - Li, Clyde Zhengdao; Chen, Zhe; Xue, Fan; Kong, Xiang T.R.; Xiao, Bing; Lai, Xulu; Zhao, Yiyu
Abstract: Prefabricated housing construction (PHC) will be widely recognized as a contributor to consumption reduction and sustainability enhancement if inherent drawbacks (e.g., fragmented management, poor connectivity) can be addressed efficiently. The promotion of advanced information and communication technologies (ICT) has triggered the evolvement of smart product-service systems (SPSS), where a smart connected product (SCP) acts as a critical role in the interconnection of physical components and specialized services for value co-creation. Hence, it is promising to realize the positive improvement of PHC based on an SPSS approach, especially during the challenging post-COVID-19 pandemic era. We developed an intelligent platform based on service-oriented manners with practical case demonstration for interactive innovation of PHC shareholders, among which prefabricated components (PC) have been defined as the SCP in PHC, and a platform-enabled approach has also been adopted in the way of SPSS. Furthermore, distributed security technology viz. blockchain along with inclusive ICT (e.g., Internet-of-Things (IoT), Cyber-Physical System (CPS), and Building Information Modeling (BIM)) are employed jointly to spark new modes of smart construction. Meanwhile, valuable exploration and open research directions are expected to facilitate the PHC supply chain to become more resilient in sustainability. Highlights: A platform-based smart product-service system of prefabricated construction is developed. Blockchain and Internet of Things are employed to promote safe data transmission and comprehensive quality supervision. Real-time monitor of schedule, cost, security in the prefabricated construction enabled sustainability innovation. Practical application seamlessly integrated with supply chain management.